Arbitrase Sebagai Alternatif Solusi Penyelesaian Sengketa Bisnis di Luar Pegadilan - Vero Arivani Caniago (Jurnal Ilmiah Wahana Pendidikan, 2022)
Alternative dispute resolution exists as a dispute resolution mechanism, compared to dispute resolution through a court mechanism which has advantages or disadvantages. Disputes that are settled out of court are often referred to as alternative dispute resolution and arbitration. In this article, the author focuses on writing disputes that are resolved out of court through arbitration. Commercial actors have great demands on arbitration because it provides benefits to the disputing parties. These advantages include mechanisms that can operate quickly, efficiently, and effectively, and the confidentiality of all parties is guaranteed and resolved by field personnel with high integrity and high skills. Because the settlement is based on good faith, the settlement of litigation through the district court is time-consuming and expensive. Subject to formal procedures to be carried out